The Interplay between Task Use, Enjoyment, Anxiety, and Willingness to Communicate in the Face-to-Face Classroom and Digital Setting among Vietnamese EFL Students - Thanh Tien Nguyen; Hung Phu Bui (Jurnal Arbitrer, 2026)
Willingness to communicate (WTC), a psychological drive for communication, is acknowledged as a burgeoning interest in language education. It can be affected by learner differences (e.g. motivation and emotion) and external factors (e.g. environment and interlocutor). Yet, little research has investigated the impacts of classroom task values and learners’ emotions on learners’ WTC across different learning modalities. This study examines the impact of perceived values of tasks on learners’ WTC in the traditional class and digital setting. Two emotional constructs, namely enjoyment and anxiety, were included as mediating factors. Data were collected from questionnaires administered to 277 Vietnamese students (n = 277) of B1-level English proficiency at a language centre in Vietnam. We utilized a structural equation modelling approach to understand the associations among the variables. Data were entered into SPSS Statistics 26 and Amos 24 for analysis. We initially tested the hypotheses before examining the hypothesized model. Results indicate that task use positively affected enjoyment and negatively determined anxiety. Enjoyment and anxiety directly affected in-class WTC positively and negatively respectively. In-class WTC was in turn a positive antecedent of digital WTC. The study suggests employing meaningful tasks and establishing a low-anxiety learning environment to increase learners’ WTC in the physical classroom and digital settings.